Perancangan Desain UI/UX Aplikasi Manajemen Inventori Barang di Pasar Tradisional Menggunakan Metode Design Thinking - Ardian Priminggadi (Fakultas Ilmu Komputer, 2025)
Traditional markets, specifically Pasar Jajag, still rely on manual recording methods for inventory management. This condition often leads to stock data discrepancies, losses due to damaged or out-of-stock items, and time inefficiency for merchants. On the other hand, buyers often face difficulties in obtaining real-time information regarding product availability before shopping, which negatively impacts the shopping experience. This study aims to design the User Interface (UI) and User Experience (UX) of a mobile-based inventory management application to address these issues. The method used is Design Thinking, consisting of Empathize, Define, Ideate, Prototype, and Test stages. Data collection was conducted through interviews with merchants and buyers, which were then developed into a High-Fidelity Prototype. The design testing was performed using the Maze platform to measure task effectiveness and the UMUX (Usability Metric for User Experience) method to measure user satisfaction. Maze testing results showed a Success Rate of 100% for the main tasks of both merchants and buyers. The UMUX evaluation yielded an average score of 87.5 for merchants and 83.33 for buyers, both of which fall into the Acceptable category. In conclusion, this application design proves to be solution-oriented and user-friendly in assisting merchants' stock management and providing information transparency for buyers in traditional markets.
Reuploud repository Hasyim Juli 2026 Validasi dan Finalisasi Ratna 6 Juli 2026
Keywords: Design Thinking; Inventory Management; Traditional Market; UI/UX; UMUX